Tiroiditis De Quervain : Pemeriksaan, Diagnosis, dan Tatalaksana - Ni Komang, Sanca Dara Dahnitha; Muhammad Ghifari Rifansha; Paradini Sukma Candra; Putu Cicilia Rarasati Kuta; Eva Triani (Faculty of Medicine, Universitas Mataram, 2023)
Thyroiditis is an inflammation that occurs in the thyroid gland and can affect the functioning of the thyroid gland. Based on its etiology, thyroiditis is distinguished into 2, namely thyroiditis which in its clinical manifestations causes pain and does not cause pain in the neck. De Quervain's thyroiditis is the most frequent cause of neck pain. Based on research, this disease is more common in women, which is about 3-4 times more than men. The clinical manifestations that arise vary, ranging from neck pain, symptoms such as hyperthyroidism, to symptoms of thyrotoxicosis. The diagnosis of De Quervain’s thyroiditis can be clinically established based on the results of physical examination and laboratory findings. The findings of laboratory examination results generally occurred an increase in LEDs, CRP, FT3, FT4, and a decrease in TSH levels. The management of this disease is divided into 3, namely supportive therapy, pharmacological, and monitoring.